Penerapan Islamic Marketing Mix dalam Mengkatkan Penjualan pada Produk Lokal Rengginang Cap Jempol di Desa Prenduan Kecamatan Pragaan Sumenep - Helliyati; Nadhifatut Thaharoh; Subai'dah (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2022)
This study aims to determine the application of the Islamic Marketing mix marketing strategy on local products Rengginang Cap Jempol UD Practical Sumenep Regency. This type of research uses qualitative research. Data collection techniques used are interviews, observation, and documentation. The result of this research is that the Islamic Marketing mix applied by Rengginang Cap thumb UD Practical can increase its sales. What was originally only sold to ordinary consumers has now achieved international sales, providing innovative products, at prices that are in accordance with Islamic law, HR actors who also follow Islamic laws, and polite in providing services to consumers.